Investment in Workforce Psychological Well-being: Strategic Returns and Theoretical Foundations - DEGHMANE , BOUAKER SEDDIK; Rabah Allah , Abdelkader (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2025)
This study aims to analyze the issue of psychological well-being in the workplace, by reviewing basic theoretical concepts and influencing factors. The study emphasizes a clear distinction between the concepts of "mental health" (defined as the absence of disorders and pathological symptoms, measured by negative indicators like anxiety and stress) and "psychological well-being" (considered a broader state of emotional, social, and occupational flourishing, including feelings of satisfaction, happiness, and accomplishment, measured by positive indicators such as job satisfaction and engagement). The study adopts an analytical methodology of psychological well-being literature, based on three main theoretical approaches: the causal approach focusing on objective factors in the work environment such as workload and organizational climate to identify the causes of psychological problems, the cognitive approach highlighting the role of individual perception and evaluation of stressors and how individuals adapt to them, and the psychodynamic approach addressing the interaction between internal individual dynamics, the work environment, and subjective and social aspects. The study seeks to understand how investing in workforce psychological well-being can achieve strategic returns for organizations. Findings indicate a positive relationship between promoting psychological well-being and increased productivity and reduced absenteeism rates. The study concludes the importance of adopting a comprehensive perspective on psychological well-being in the workplace and understanding the theoretical foundations supporting this direction. It also offers practical strategies to improve psychological well-being, such as promoting work-life balance through flexible work arrangements, providing job security and a sense of stability building strong social support networks in the workplace like mentoring programs, improving the physical work environment by providing comfortable and healthy spaces, and recognizing employee achievements to increase their sense of appreciation. Investing in psychological well-being is not merely an ethical responsibility but an economic investment with tangible returns that contributes to attracting and retaining talent.